STUDI HADIS: PEMETAAN HADIS MARDUD KARENA SANADNYA TERPUTUS - jufriyadi sholeh (Reflektika, 2021)
Every hadith that reaches the generation of the Islamic age, starting from the early generation of Islam, namely the era of friends, to the next generations, will always be validated by hadith experts to assess the quality of the hadith. Hadith scholars have also carried out mappings of hadith from various aspects, especially from the part of its quality. Mapping hadith from the element of its quality is the leading study in hadith studies. In hadith study books, the material for discussing the quality of hadith is the main goal to be understood, so that hadith students can distinguish hadiths that are Maqbul or Mardud. Among the specific Hadith, mappings are mapping the Mardud hadith because the Sanad hadith is not continuous or disconnected. The mapping of hadith from this aspect is an important part of studying because although Sanad is of low-quality value, Mardud hadith in the disconnected of Sanad still has I'tibar value in hadith criticism, that is, it can be calculated to ascend to Hasan li Ghairih. It can even support other hadiths when there is a contradiction to performing the Tarjih. Mardúd hadith because the Sanad is disconnected, there are six kinds, namely: four kinds of real disconnected, which include 1) Mu'allaq hadith, 2) Mursal hadith, 3) Mu'dhal hadith, 4) Munqathi' hadith and two kinds vaguely disconnected covering:1) Mudallas hadith and 2) Mursal khafí hadith.